PELANGGARAN ETIKA PROFESI AKUNTANSI MANIPULASI LAPORAN KEUANGAN PT KERETA API INDONESIA - Novita, Ema; Tekege, Tekege; Sarindawati, Sarindawati; Sabariah, Etika (Ensiklopedia of Journal, 2024)
This research is motivated by the existence of phenomena and incidents of fraud committed by professional accountants in carrying out accounting practices and misuse of financial reports due to the erosion of ethics and morality. Accounting ethical practices uphold honesty, confidentiality, professionalism, competence and prudence within the entity. The purpose of this research is to determine the violations that occurred at PT Kereta Api Indonesia (KAI) in 2024. Accountant professional ethics are intended as guide lines and rules for all members, both those who practice as auditors, government workers and private workers.There search method that will be carried out is the library research method or literature study by obtaining the necessary information through journals, books orother sources that are related to there search topic. This researchis a descriptive analysis which aims to provide a description or explanation of phenomena or events.This research source of data collection is secondary data, namely through scientific journals on Google Scholar, news sites and other reliable websites, and media valid in publishKeywords:Accountant professional ethics,Violation, PT Kereta Api Indonesia, Fraud